Current clinical practice of orofacial contracture management in head and neck burn patients among physical therapists of Hyderabad - Shaikh, Rabia; Fakhrah Safdar; Hussain, Shujaat (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the current clinical practices of orofacial contracture management among physical therapists dealing with head and neck burn patients. Method: The cross-sectional observational study was conducted at the Isra Institute of Rehabilitation Sciences, Hyderabad, Pakistan, from May 14 to December 31, 2021, and comprised physical therapistsworking in different hospitals and clinics and having clinical experience >1 year. Data was collected using a questionnaire based on literature which included questions related to demographics, service provision, clinical training, orofacial burn wound assessment, orofacial contracture intervention and outcome measurement in multiple choice, dichotomous or open response formats. Data was analysed using SPSS 22. Results: Of the 100 subjects, 38(38%) were males and 62(62%) were females, while 71(71%) were aged 20-30 years, 22(22%) were aged 31-40 years, and 7(7%) were aged 41-50 years. Besides, 57(57%) physical therapists used stretching/exercise in the management of superficial-partial thickness burn, while 49(49%) used it in deep-partial thickness burn, and 44(44%) in full-thickness burn. Also, 43(43%) therapists used presence or maturation of the scar tissue as the indicator to escalate/reduce the intensity of the treatment. Regarding splinting, 49(49%) therapists used it on the 5th day of grafting and 35(35%) used it after complete healing. Conclusion: There was minimal knowledge regarding the use of specific interventions and specific regimes at particular stages. Key Words: Head burn, Neck burn, Orofacial contracture, Contracture management, Physical therapist.